Indicadores de Desempenho para o Sistema de Bibliotecas da Universidade Federal do Amazonas (SISTEBIB/UFAM) - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The research focused on the eight Sectorial Libraries of UFAM, located in Manaus. Aiming to propose performance indicators for SISTEBIB/UFAM. For a better understanding of the context studied, was opted for qualitative and exploratory research. We used the literature review to take stock of the main indicators used in the assessment of University Libraries. The study was of an applied nature, it generated knowledge to practical application, directing them to the solution of specific problems. To examine the scenario in which it is inserted SISTEBIB/UFAM was performed situational diagnosis of System, where presents its organizational structure, its material and human resources, also presents the strengths and weaknesses of the System, result of the analysis carried out in the data collected from the crowded servers in the eight Sectorial Libraries. With the result of this study it was possible to build an instrument capable of measuring the performance of the services offered by BS's, as well as the level of satisfaction of its users, it that will contribute to the system’s management follow if their objectives are being achieved or not, always seeking measures that enable follow up the demands of its users.
Keywords: Biblioteca universitária; Indicadores de desempenho; Avaliação de desempenho; University library; Performance indicators; Performance evaluation; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO: GERENCIA DE PRODUÇÃO